Respon Pertumbuhan Hasil Sambung Pucuk Akibat Pemberian Sitokinin Pada Beberapa Varietas Lengkeng - Yudi Rumawan; Surya Mulya , Agus; Rakhmi Indriana , Kovertina (Fakultas Pertanian Universitas Winaya Mukti, 2025)
This research focuses on the response of graft growth in various longan (Dimocarpus longan Lour.) varieties to cytokinin application. Longan is a high-value fruit commodity known for its sweet taste, easy peeling, and health benefits due to its rich content of vitamins and beneficial compounds such as flavonoids and amino acids. The study aims to examine the influence of cytokinin, a plant growth hormone, on the compatibility of grafting in longan plants and its potential to improve seedling quality. Specifically, the research evaluates four longan varieties: Diamond River, Kateki, Itoh, and Pingpong, to identify the most effective cytokinin concentration for optimal growth. The study was conducted using a randomized block design (RBD) factorial with two variables: cytokinin concentration and longan variety. Results showed no significant interaction between the concentration of cytokinin and the different longan varieties. The study concludes that cytokinin does not have a notable effect on graft growth across the tested longan varieties. Further research is recommended to evaluate other factors, such as extended observation periods and different growth regulators, to improve the efficiency of longan grafting techniques. Keywords: cytokinin; Diamond River, Kateki, Itoh, and Pingpong